Linking internal and external bacterial community control gives mechanistic framework for pelagic virus‐to‐bacteria ratios. (5th July 2016) - Våge, Selina; Pree, Bernadette; Thingstad, T. Frede
Summary: For more than 25 years, virus‐to‐bacteria ratios (VBR) have been measured and interpreted as indicators of the importance of viruses in aquatic ecosystems, yet a generally accepted theory for understanding mechanisms controlling VBR is still lacking. Assuming that the denominator (total bacterial abundance) is primarily predator controlled, while viral lysis compensates for host growth rates exceeding this grazing loss, the numerator (viral abundance) reflects activity differences between prokaryotic hosts. VBR is then a ratio between mechanisms generating structure within the bacterial community and interactions between different plankton functional types controlling bacterial community size. We here show how these arguments can be formalized by combining a recently published model for co‐evolutionary host‐virus interactions, with a previously published "minimum" model for the microbial food web. The result is a framework where viral lysis links bacterial diversity to microbial food web structure and function, creating relationships between different levels of organization that are strongly modified by organism‐level properties such as cost of resistance.